Ageing stereotypes influence the transmission of false memories in the social contagion paradigm. Issue 3 (16th March 2019) - Numbers, Katya T.; Barnier, Amanda J.; Harris, Celia B.; Meade, Michelle L.
ABSTRACT: These experiments are the first to investigate the impact of confederate accuracy, age, and age stereotypes in the social contagion of memory paradigm. Across two experiments, younger participants recalled household scenes with an actual (Experiment 1) or virtual (Experiment 2), older or younger confederate who suggested different proportions (0%, 33% or 100%) of false items during collaboration. In Experiment 2, positive and negative age stereotypes were primed by providing bogus background information about our older confederate before collaboration. Across both experiments, if confederates suggested false items participants readily incorporated these into their own memory reports. In Experiment 1, when no age stereotype was primed, participants adopted similar proportions of false items from younger and older confederates. Importantly, in Experiment 2, when our older confederate was presented in terms of negative ageing stereotypes, participants reported less false items and were better able to correctly identify the source of those false items.